1998
DOI: 10.1021/ic980349b
|View full text |Cite
|
Sign up to set email alerts
|

B-DNA Binding with Cobalt(III) and Vanadyl(2+) Derivatives of Tetracationic 5,10,15,20-Tetrakis(4-N-methylpyridyl)porphine:  Combined CD, Optical, and Electronic MCD Spectra

Abstract: Electronic MCD is used for the first time to obtain electronic and geometric structural insight into the free and DNA-bound states of the six-coordinate CoIII and VO2+ derivatives of 5,10,15,20-tetrakis(4-N-methylpyridyl)porphine. Correlations between MCD, CD, and optical spectra measured in the porphyrin Soret band (or B0) region, and FLDr literature data, are consistent with each metalloporphyrin having a face-on orientation in the major groove of CT DNA, sites 5‘AT3‘ and 5‘CG3‘ being preferred, and with por… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…A major groove binding mode that corresponds the "outside binding" was proposed for CoTMPyP based on combination of the magnetic CD spectrum and the binding angles measured by LD at a low [porphyrin]/[DNA base] ratio. 46 42°, which were previously reported for the CoTMPyP−DNA complex, 45 were used as evidence for the major groove binding geometry. However, the former angle was obtained from the average LD r value in the Soret region, whereas the latter was obtained from the assumption that the two electric transition moments were completely degenerate.…”
Section: ■ Discussionmentioning
confidence: 99%
“…A major groove binding mode that corresponds the "outside binding" was proposed for CoTMPyP based on combination of the magnetic CD spectrum and the binding angles measured by LD at a low [porphyrin]/[DNA base] ratio. 46 42°, which were previously reported for the CoTMPyP−DNA complex, 45 were used as evidence for the major groove binding geometry. However, the former angle was obtained from the average LD r value in the Soret region, whereas the latter was obtained from the assumption that the two electric transition moments were completely degenerate.…”
Section: ■ Discussionmentioning
confidence: 99%
“…This binding mode is in competition with intercalation. Exceptions in the binding mode have also been suggested for various porphyrins (Kuroda and Tanaka, 1994;Sehlstedt et al, 1994;Schneider and Wang, 1994;Lipscomb et al, 1996;Yun et al, 1998;Barnes and Schreiner, 1998). When Cu(II) [meso-tetra(N-methyl-4-pyridyl)porphyrin] forms a complex with hexamer duplex [d(CGATCG)] 2 , porphyrin intercalates: the cytosine base of 5ЈCGA3Ј flips out from DNA (Lipscomb et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…When Cu(II) [meso-tetra(N-methyl-4-pyridyl)porphyrin] forms a complex with hexamer duplex [d(CGATCG)] 2 , porphyrin intercalates: the cytosine base of 5ЈCGA3Ј flips out from DNA (Lipscomb et al, 1996). This result from an x-ray structure was criticized later by NMR study (Barnes and Schreiner, 1998). The groove binding mode, mainly based on the extensive circular dichroism (CD) and linear dichroism (LD) study was also suggested (Kuroda and Tanaka, 1994;Sehlstedt et al, 1994;Schneider and Wang, 1994;Lipscomb et al, 1996;Yun et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the MCD spectra were used to confi rm the binding mode by comparing the excitedstate angular momentum (L j ), which is proportional to ([∆θ] p-t /ε max ) of free and DNA-bound porphyrins, i.e. the energy levels of the Soret band MOs (1a 1u 3a 2u 4e g ) of porphyrins [24,25,[37][38][39][40]. Comparing the L j of porphyrin before and after binding to DNA is of interest because the interaction of the Soret band MOs of porphyrin with the low-symmetry B-DNA sites can lead to a change in L j , and the magnitude of this change is expected to be proportional to the degree of interaction.…”
Section: Spectral Measurementsmentioning
confidence: 99%
“…It has also been shown that the binding mode of porphyrins to the nucleic acid duplex, e.g. intercalative or outside binding mode, can also be tuned by varying the metal center and the thickness of the complex molecule based on the presence or absence of axial ligands [13,[23][24][25][26][27]. Thus, the thin square planar copper(II) derivatives of H 2 TMPyP and H 2 PzP are capable of intercalation, because these metalloporphyrins are not ligated at their vacant axial site by aquo ligands and can intercalate into the pocket between two adjacent, closely spaced (3.4 Å) base pairs of B-DNA.…”
Section: Introductionmentioning
confidence: 99%